Ratio Legis Of The Principle Of Sovereignty In The Regulation Of Plantation Business As A Settlement Of Land Disputes/Conflicts - Hairan Hairan; Imam Koesahyono; Tunggul Anshori Setia Negara; Bambang Sugiri (CV. AFDIFAL MAJU BERKAH, 2024)
Plantation businesses have existed since the past, especially growing rapidly during the Dutch colonial era. The Dutch Colonial Government then made several laws and regulations regarding the regulation of land . Currently, plantations are under the umbrella of the Plantation Law and UUCK. In terms of Legis ratio, the inclusion of